2023
DOI: 10.1080/07853890.2023.2187877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perioperative outcomes and anesthetic-related complications of morbidly obese and super-obese parturients delivering by cesarean section

Abstract: Objective To compare the perioperative outcomes and anesthetic-related complications of morbidly obese and super-obese parturients delivering by cesarean section. Methods A retrospective analysis of 6 years of data was performed. Exclusions were cases with gestational ages <24 weeks, placenta accreta spectrum, polyhydramnios, or multiple gestations. Results The study included 494 patients whose body mass index (BMI) exceeded 40 kg/m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Thromboembolism also can be a cause of cardiac arrest in the peripartum period and is a significant concern for obese parturients [ 10 ]. Reports have demonstrated cases of cardiac arrest resulting from pulmonary embolism in morbidly obese parturients during the perioperative period [ 11 , 12 ]. Given the absence of thromboprophylaxis in our patient, thromboembolism should be considered as a potential differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboembolism also can be a cause of cardiac arrest in the peripartum period and is a significant concern for obese parturients [ 10 ]. Reports have demonstrated cases of cardiac arrest resulting from pulmonary embolism in morbidly obese parturients during the perioperative period [ 11 , 12 ]. Given the absence of thromboprophylaxis in our patient, thromboembolism should be considered as a potential differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study included women with a BMI > 40 kg/m 2 [27]. Although we collected blood samples before and after the bariatric surgery, we could not repeat the experiment one year later to investigate the gene expression further.…”
Section: Discussionmentioning
confidence: 99%
“…Previous and recent studies found that in morbidly obese patients undergoing cesarean delivery, the incidence of intra-operative and post-operative complications including gestational diabetes, preeclampsia, hypotensive episodes, post-partum hemorrhage (PPH), preterm birth, stillbirth, neonatal seizures, and macrosomia were significantly higher than in non-obese patients [5][6][7][8]. Hence, morbidly obese patients require special consideration during labor, delivery, and post-partum care.…”
Section: Discussionmentioning
confidence: 99%